Етнокультурний профіль третьої хвилі української еміграції - Антонюк, Т. (Народна творчість та етнологія, 2020)
У статті досліджено окремі книжкові видання з фонду відділу зарубіжної україніки Національної бібліотеки України імені В. І. Вернадського, які розкривають історію третьої хвилі української еміграції (1945 – кінець 1980‑х рр.), спричиненої Другою світовою війною (1939–1945). Увагу приділено виданням діаспори, а також вітчизняним, що вийшли з друку у другій половині ХХ – на початку ХХІ ст. Акцентовано увагу на виданнях, що розкривають особливості, характер, чисельність, роль і внесок третьої хвилі у збереження національної ідентичності українства, розвиток національної ідеї та боротьбу за відновлення української державності. Встановлено, що книжкові видання представляють різні види друкованої продукції: довідкової, наукової, мемуарної, художньої, навчальної. Вагому частину становлять довідкові видання з історії української еміграції, у яких висвітлено третю її хвилю, а також розповіді учасників і очевидців тих подій, які свідчать про поневіряння «переміщенців» у таборах, їхні пошуки пристановища у світі. Меншою кількістю представлено монографії, документальні видання та художню літературу. Розкрито роль і значення видань про третю хвилю української еміграції для осягнення феномену світового українства. Відзначено, що з проголошенням незалежності України, третю хвилю української еміграції розпочали активно досліджувати вітчизняні вчені. Це втілилося в публікації низки праць, що зберігаються в колекції «Підручний фонд». The article considers separate book editions from a fund of the Foreign Ukrainian Studies Department of the V. Vernadskyi National Library of Ukraine, which reveal the history of the third wave of Ukrainian emigration (1945 to late 1980s) brought forth by the Second World War (1939–1945). Attention is paid to editions of Ukrainian diaspora’s publishing houses issued in countries of mass settlement of the Ukrainians. A separate publication presents a book feature and emphasizes the importance of this literature for forming a holistic view of Ukrainian emigration’s history as an integral component of Ukrainian history. An emphasis is placed on publications that expose peculiarities, nature, numbers, role, and contribution of the third wave in preserving the national identity of the Ukrainians, as well as developing a national idea and fighting for the restoration of Ukrainian statehood. It is established that book editions represent different types of printed matter: reference, science, memoirs, science-journalism, education, belles-lettres, published mainly in the second half of the 20th century. A significant portion of the publications is constituted by editions in the realm of Ukrainian emigration’s history, which shed light on its third wave, as well as evidences of the then developments’ participants and eyewitnesses, which are indicative of distresses suffered by the displaced persons in camps, and their search for a shelter. Fewer are represented by monographs, documentaries, and belles-lettres. There have been also revealed a role and the significance of editions on the third wave of Ukrainian emigration for understanding the phenomenon of the global Ukrainianhood. It is noticed that since the proclamation of Ukraine’s independence, domestic scholars have begun actively studying the third wave of Ukrainian emigration. This was embodied in publishing a number of works: monographs, textbooks on the history of Ukraine, and reference books, which are stored in the collection Handy Fund.